The oxymoron of a benevolent authoritarian leadership: the case of Lebanon’s Hezbollah and Hassan Nasrallah - Filippidou, Anastasia (Taylor and Francis, 2020)
Leadership entails both continuity and an ever-changing relationship between a number of factors, including the leader, the context, the followers, broader society and even the pace of change. Although the above elements are not identical in all scenarios, there are still certain transcending common features allowing to draw conclusions applicable to different situations. This article focuses on the leadership of radical political movements (RPMs) in volatile and crisis situations, and the role of this leadership in the transformation process from weak and fragmented communities to peaceful and viable ones. The article uses the case of Hezbollah to test the above ideas, and examines the motives behind Hezbollah’s infitah of opening up, and its lebanonization, expressed in its ideology, political programs, and policies, leading to Hezbollah’s integration into mainstream political life, blurring the boundaries between legitimate and illegitimate politics. The research demonstrates the need for a constant balance of different and often contrasting leadership characteristics and for the adjustment of leadership styles to constantly changing situations. Lastly, the article focuses on the rigidity of state counter measures toward RPMs and their leadership, with particular emphasis on the resilience of what often appears to be outdated state counternarratives.
Keywords: Radical political movements (RPMs); transitional processes; leadership; Hezbollah; narratives and counternarratives